Current Challenges for the Postal Services Sector in the Context of E-Commerce – Predictive Analysis of V4 States - Michaela Novotná; Dalibor Gottwald (Promet - Traffic&Transportation, 2021)
The article’s focus is on the postal services sector. The sector plays an important role in a process of delivering packages to the customers. Over the last few years, there has been a significant growth in volume of shipments transported. The aim of the article is to demonstrate the current development and subsequent prediction of two selected indicators that play an important role in the context of e-commerce development in the V4 states. One of the indicators is the number of shipments; the other is the indicator of CO2 emissions. While the values of the CO2 emission in the predictive analysis in comparison with the growing e-commerce turnover indicator stagnate, the number of shipments is growing alongside the e-commerce turnover values. In the light of these findings, it is clear that the growing number of shipments will result in the need to change the approach to the organisation of the parcel delivery process, especially in big cities and agglomerations. It is also necessary to mention that organisational changes in the parcel delivery process in big cities and agglomerations must be carried out in an environmentally friendly way.